Development and evaluation of a novel training program to build study staff skills in equitable and inclusive engagement, recruitment, and retention of clinical research participants. Issue 1 (30th August 2022) - Cranfill, Jessica R.; Freel, Stephanie A.; Deeter, Christine E.; Snyder, Denise C.; Naggie, Susanna; Barrett, Nadine J.; Roberts, Jamie N.
Abstract: Background: Adequate equitable recruitment of underrepresented groups in clinical research and trials is a national problem and remains a daunting challenge to translating research discoveries into effective healthcare practices. Engagement, recruitment, and retention (ER&R) training programs for Clinical Research Professionals (CRPs) often focus on policies and regulations. Although some training on the importance of diversity and inclusion in clinical research participation has recently been developed, there remains a need for training that couples critical equity, diversity, and inclusion (EDI) concepts with skill development in effective recruitment and retention strategies, regulations, and best practices. Approach and methods: We developed the ER&R Certificate program as a holistic approach to provide Duke University CRPs the opportunity to build competency in gap areas and to increase comfort in championing equitable partnerships with clinical research participants. The thirteen core and elective courses include blended learning elements, such as e-learning and wiki journaling prompts, to facilitate meaningful discussions. Pre- and post-assessments administered to CRP program participants and their managers assessed program impact on CRP skills in ER&R tasks and comfort in equitable, diverse, and inclusive engagement of clinical research participants. Results and discussion: Results from the first two cohorts indicate that CRPs perceived growth in their own comfort with program learning objectives, especially those centered on participant partnership and EDI principles, and most managers witnessed growth in competence and responsibility for ER&R-related tasks. Results suggest value in offering CRPs robust training programs that integrate EDI and ER&R training.